"Nekaj nezaslišanega" - Saksida, Igor (Jezik in slovstvo, 2001)
The editor of a vast collection of Sovene folk poems Karle Štrekelj (1908-1923:308) added the following commnet to poems for children: :There are many things there that one would not expect from the young person and that areabhorrent to contemporary civility and prudery, which views maturalia as things unmentionable." His witty evaluation of children's folk creativity covers the key constituents of taboos in literature for children, which are still valid today.
Keywords: children's and youth literature; Štrekelj, Karel, 1859-1912; childhood; young adult literature; mladinska književnost; morality; otroštvo; moralnost; Slovene literature; slovenska književnost; slovenske ljudske pesmi; tabuji; tematika; mladinska poezija